Análisis de la calidad de suelos tratados con Biol en el campus experimental académico (CEASA), periodo 2022 - Medina Lagla, Karen Analy (2022)
The current research had as aim to analyze the Machu Picchu project land quality of the soil, through the biol different concentrations application to improve its natural condition, applying it into 4 different doses, it was developed at the Cotopaxi Technical University at 2734 meters above sea level, with an alkaline land pH (9.54), a 14.2 0 C average temperature and a 254.8 mm annual rainfall. It was applied a Completely Randomized Block Design (DBCA) and three repetitions, getting a 24 experimental units total. The trial establishment into established plants, each experimental unit was delimited lengthwise and widthwise with a I meter separation between treatments, each treatment consisted by 6 plants. The Biol application was made twice with an interval with the one month to different doses: Tl(lkg), T2(1.5Kg), T3(2Kg) and T4(2.5Kg). The present research results yielded the following data: For the land physical and chemical properties: all the treatments lowered the soil pH from 9.54 to 8.29 and it increased the organic matter (0M) percentage in the soil from 0.23 to 2.1. The treatment (T4) presented the best propenies for the eroded soil recoveries, considering, what the best results were also got into the plant height (48.33 cm), T5 as a control, it presented the lowest averages. The soil quality had a 52.5 points initial assessment, which it was considered fair, and after treatment, it got 62.5 points, it considered good, according to the ISQ scale. When making a comparison with another soil improver biol, it called Fertibiol, it can conclude, what the elaborated biol presents 38.23% of efficiency in comparison to the biol under discussion. Taking into account, which it presents significant advantages and it complies with all the suggested parameters by the current Environmental Regulations.